2006
DOI: 10.1002/elan.200503458
|View full text |Cite
|
Sign up to set email alerts
|

Complex Formation in the Region of Metal Hydrolysis and M(OH)2 Precipitation. A Glass Electrode Potentiometric and Polarographic Study of Cd–(AMPSO)x–(OH)y and Zn–(AMPSO)x–(OH)y Systems

Abstract: The interaction between cadmium or zinc and AMPSO was investigated by DCP and GEP, at fixed total ligand to total metal concentration ratios and various pH values, at 25.0 8C and 0.1 M KNO 3 ionic strength. For Cd -(AMPSO) x -(OH) y system, CdL and CdL(OH) species, were identified, with stability constants values set to (as log b): 2.1 AE 0.1 and 6.2 AE 0.2, respectively. For Zn -(AMPSO) x -(OH) y system, the proposed final model with stability constants set to (as log b) is: ZnL ¼ 2.5 AE 0.1 and ZnL(OH) 2 ¼ 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Above this pH, the lability of the complexes is lost, and we observed a strong decrease of the peak current, indicating the formation of insoluble, electrochemically inactive, hydrolytic species (Machado et al, 2006). This assumption was confirmed by cyclic voltammetry (CV) measurements, in which we did not observe the typical curve of a reversible process.…”
Section: Resultssupporting
confidence: 63%
“…Above this pH, the lability of the complexes is lost, and we observed a strong decrease of the peak current, indicating the formation of insoluble, electrochemically inactive, hydrolytic species (Machado et al, 2006). This assumption was confirmed by cyclic voltammetry (CV) measurements, in which we did not observe the typical curve of a reversible process.…”
Section: Resultssupporting
confidence: 63%
“…Studies about AMPSO complexation have shown that this buffer has the ability to bind with Ca, Co, Cu, Pb, Mg, Mn and Ni. 42,43,[62][63][64][65] …”
Section: Propanol Familymentioning
confidence: 99%
“…This was not the case for PeiW in the presence of Mg 2+ where similar activities were seen at comparable pH values of Bistris propane buffer and Ampso (not shown). Ampso can form complexes with divalent metal ions [ 31 , 32 ]. The lower activity using Ampso in the presence of Ca 2+ may possibly be due to complex formation between Ca 2+ and Ampso, while there may not be complexes formed to the same extent between Mg 2+ and Ampso.…”
Section: Resultsmentioning
confidence: 99%